MAJĀZ MURSAL DALAM QS. AL-BAQARAH AYAT 153–177: KAJIAN ʿILM AL-BAYĀN - Ahmad Syamsuri Syam; Mohamad Harjum; Haniah Haniah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
This study analyzes the stylistic phenomenon of majāz mursal in Q.S. Al-Baqarah verses 153–177, a cohesive thematic unit of the Qurʼan encompassing the obligation of patience (ṣabr), Islamic rites (shaʼāʼir), and legal rulings (aḥkām). Majāz mursal is a sub-type of majāz lughawī in which a word is used beyond its literal meaning based on a relationship other than resemblance (ʿalāqah ghair mushābahah), accompanied by a contextual indicator (qarīnah) preventing literal interpretation. The research employs a descriptive-analytical method anchored in classical balāghah theory, drawing on classical and contemporary scholarship. Five instances of majāz mursal are identified across QS. 2:153, 157, 158, 168, and 177, representing five distinct relational types: sababiyyah, musabbabiyyah, kulliyyah, juzʼiyyah, and maḥalliyyah. Findings show that these figurative expressions serve semantic, rhetorical, and theological functions that deepen Qurʼanic meaning far beyond literal signification, constituting a divine communicative strategy (istirātījiyyah tawāṣuliyyah ilāhiyyah) that conveys dense, multi-layered meanings with remarkable concision, reflecting the inimitable literary quality (iʼjāz bayānī) of the Qurʼan.